The Long-Term Cardiovascular Risks of Proton Pump Inhibitors (PPIs): A Meta-Analysis of Observational and Randomized Trials - Abbas, Muhammad Raza; Hussain , Hamna; Abbas, Mudassir; Qazi, Urooba; Rafique, Mamoona; Batool , Iqra; Mir, Adeen (Indus Journal of Bioscience Research, 2025)
Background: Proton pump inhibitors (PPIs) are widely used for the treatment of acid-related disorders, such as gastroesophageal reflux disease (GERD) and peptic ulcers. However, emerging evidence suggests that long-term PPI use may be associated with an increased risk of adverse cardiovascular events, including ischemic stroke, myocardial infarction, cardiac arrest, and cardiovascular mortality. Despite numerous observational studies and randomized controlled trials (RCTs) investigating this association, the evidence remains inconclusive. Objective: This meta-analysis aims to evaluate the long-term cardiovascular risks associated with PPI use, analyzing pooled data from both observational studies and RCTs to assess the impact of PPIs on ischemic stroke, myocardial infarction, cardiac arrest, and cardiovascular mortality. Methods: A systematic literature search was conducted in PubMed, Embase, Cochrane Library, and Web of Science to identify eligible studies. Inclusion criteria required studies to report cardiovascular outcomes in PPI users compared to non-users, placebo, or H2 blockers, with a minimum follow-up of two years. Data extraction and risk of bias assessment were conducted independently by two reviewers. Pooled effect sizes were calculated using a random-effects model, and heterogeneity was assessed using the I² statistic. Subgroup analyses were performed based on age, PPI dosage, and study design. Publication bias was evaluated using Egger’s and Begg’s tests, with statistical significance set at p < 0.05. Results: Eight studies, including 8,356 participants, were included in the meta-analysis. PPI use was significantly associated with an increased risk of ischemic stroke (OR: 1.18, 95% CI: 1.09–1.28, p < 0.001, I² = 32%), myocardial infarction (OR: 1.25, 95% CI: 1.14–1.38, p < 0.001, I² = 45%), cardiac arrest (OR: 1.42, 95% CI: 1.19–1.71, p < 0.01, I² = 51%), and cardiovascular mortality (OR: 1.21, 95% CI: 1.12–1.31, p < 0.001, I² = 38%). Subgroup analysis revealed that the risk was higher in older adults (>60 years, OR: 1.30, 95% CI: 1.19–1.42, p < 0.001) and those receiving high-dose PPI therapy (OR: 1.35, 95% CI: 1.22–1.49, p < 0.001, I² = 52%). No significant publication bias was detected. Conclusion: This meta-analysis links long-term PPI use to higher risks of cardiovascular events, especially in older adults and high-dose users. Clinicians should evaluate prolonged use carefully. Large-scale RCTs are needed for confirmation.